Aluminum chloride intercalated natural graphite derived negative electrode material and preparation method thereof, lithium ion battery negative electrode plate and lithium ion battery

By introducing aluminum chloride into the negative electrode material of lithium battery and heat treatment, the graphite sheet spacing and specific surface area are expanded, and the performance problem caused by the small graphite sheet spacing in the prior art is solved, and the electrochemistry of lithium-ion batteries is significantly improved Performance and stability.

CN119208598APending Publication Date: 2024-12-27CHONGQING INNOVATION CENTER OF BEIJING INSTITUTE OF TECHNOLOGY +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411360478.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-25
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The graphite sheet spacing of the negative electrode materials of existing lithium batteries is small, resulting in poor performance of lithium batteries in the first reversible capacity, first-week Coulomb efficiency, rate performance, cycle performance and capacity retention rate, and cannot meet high performance requirements.

Method used

By introducing aluminum chloride into the natural graphite sheets, heat treatment is performed to expand the sheet spacing and specific surface area, forming an aluminum chloride intercalation compound, reducing lattice stress and oxygen-containing functional groups, and improving material stability and capacity.

Benefits of technology

It significantly improves the first reversible specific capacity, first-week Coulomb efficiency, rate performance and cycling performance of lithium-ion batteries, maintains high capacity and stability, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208598A_ABST
    Figure CN119208598A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and discloses an aluminum chloride intercalated natural graphite derived negative electrode material and a preparation method thereof, a lithium ion battery negative electrode plate and a lithium ion battery. The negative electrode material comprises natural graphite and aluminum chloride between natural graphite sheet layers; wherein the interlayer spacing of the negative electrode material ranges from 1.282 nm to 1.298 nm. The aluminum chloride is introduced between natural graphite sheet layers, so that the spacing between the natural graphite sheet layers in the negative electrode material and the specific surface area of the negative electrode material can be enlarged, and part of structural defects are introduced into the negative electrode material, so that the negative electrode material has higher capacity; therefore, the lithium ion battery containing the negative electrode material has improved first reversible specific capacity, first-cycle coulombic efficiency, rate capability, cycle performance, capacity and capacity retention ratio. According to the preparation method of the negative electrode material provided by the invention, lattice stress and oxygen-containing functional groups in natural graphite in the negative electrode material can be reduced through heat treatment, so that the stability and the capacity of the negative electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a negative electrode material derived from natural graphite with aluminum chloride intercalation and a preparation method thereof, a negative electrode sheet for a lithium ion battery and a lithium ion battery. Background Art

[0002] With the rapid development of the global economy, people have gradually realized that fossil fuels are becoming increasingly depleted and their harm to the environment. Developing green, pollution-free renewable energy is an effective way to solve energy and environmental problems. In recent years, lithium-ion batteries have been widely used in portable electronic devices, electric vehicles and other fields due to their high capacity and long cycle life.

[0003] Since the development of lithium-ion batteries, a variety of positive electrode material systems have been studied, but the graphite-based negative electrode material system has been used to this day. Graphite-based negative electrode materials are the most commonly used negative electrode materials for lithium-ion batteries. They have the advantages of high energy density, low voltage, good electrical conductivity, and abundant resources. They will be the first choice for negative electrode materials for lithium-ion batteries for a long time in the future. Currently, graphitized carbon (natural flake graphite, graphitized mesophase carbon microspheres, artificial graphite, etc.) and non-graphitized carbon (soft carbon, hard carbon, etc.) have been studied. In the context of the dual markets of power lithium batteries and consumer lithium batteries, artificial graphite and natural graphite negative electrode materials have developed into the mainstream of the market, occupying more than 90% of the market share for a long time.

[0004] Natural graphite negative electrode materials are mainly made of flake graphite, but they have the following disadvantages: (1) flake graphite has a small specific surface area and low initial charge and discharge efficiency; (2) it is anisotropic, which is not conducive to Li + (3) Cracks will form between the sheets due to the insertion and extraction of lithium ions, thereby increasing the Li + Diffusion resistance. At present, the traditional graphite negative electrode can no longer meet the growing high performance requirements. For this reason, a large number of scholars at home and abroad have been actively exploring modification technologies.

[0005] CN117199328A discloses a silicon-carbon negative electrode material with high silicon content and a preparation method thereof, wherein natural flake graphite is used as a precursor, metal chloride is inserted into the interlayer spacing of natural graphite to form a graphite interlayer compound, and then the chloride is decomposed by high temperature treatment to produce gas expansion, thereby preparing expanded graphite with controllable interlayer spacing and ample interlayer space; using this as a carrier, nano silicon particles are deposited between graphite layers by pyrolysis of silane to form a composite material; finally, a dense and uniform carbon layer is coated on the surface of the material by pyrolysis of a gas phase carbon source, thereby obtaining a silicon-carbon composite material that can be used as a negative electrode material for lithium ion batteries. The large interlayer space of the graphite is not only conducive to the deposition of more silicon particles, but also the silicon particle content is more than 70%, and the composite material exhibits a higher capacity; at the same time, the extra space between the layers is conducive to buffering the volume expansion of silicon, maintaining the structural stability of the material, and exhibiting better cycle performance. However, the silicon-carbon negative electrode material also includes nano-silicon particles, and there is a lack of chloride support between the graphite sheets. As the number of battery cycles increases, the spacing between the graphite sheets will decrease, affecting its cycle performance and capacity retention rate.

[0006] Therefore, there is an urgent need to develop a natural graphite-derived negative electrode material with aluminum chloride intercalation and a preparation method thereof, a lithium-ion battery negative electrode sheet and a lithium-ion battery, which have excellent performance in terms of first reversible specific capacity, first-week coulombic efficiency, rate performance, cycle performance, capacity and capacity retention rate. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems in the prior art that the graphite surface area in the negative electrode material of a lithium battery is small and the spacing between graphite sheets is small, resulting in the lithium battery having a low first reversible specific capacity, first cycle coulombic efficiency, rate performance, cycle performance, capacity and capacity retention rate, and to provide a lithium ion battery negative electrode material and a preparation method thereof, a lithium ion battery negative electrode sheet and a lithium ion battery.

[0008] In order to achieve the above object, the present invention provides a first aspect of a negative electrode material for a lithium ion battery, wherein the negative electrode material comprises natural graphite and aluminum chloride between natural graphite sheets;

[0009] Wherein, the interlamellar spacing of the negative electrode material is 1.282-1.298 nm.

[0010] A second aspect of the present invention provides a method for preparing a negative electrode material for a lithium ion battery, wherein the preparation method comprises the following steps:

[0011] After mixing natural graphite and aluminum chloride, heat treatment is performed to obtain a negative electrode material;

[0012] Wherein, the mass ratio of the natural graphite to aluminum chloride is 1:(5-20);

[0013] The heat treatment conditions include: under protective gas, heating from room temperature to 160-200° C. at a heating rate of 3-8° C. / min for 5-20 hours.

[0014] The third aspect of the present invention provides a negative electrode material prepared by the above preparation method.

[0015] A fourth aspect of the present invention provides a negative electrode plate for a lithium ion battery, wherein the negative electrode plate for the lithium ion battery comprises the negative electrode material described above.

[0016] A fifth aspect of the present invention provides a lithium ion battery, comprising the above-mentioned lithium ion battery negative electrode sheet.

[0017] Through the above technical solution, the technical solution provided by the present invention achieves the following beneficial effects:

[0018] (1) The negative electrode material provided by the present invention includes natural graphite and aluminum chloride between natural graphite flakes. Introducing aluminum chloride between natural graphite flakes can expand the natural graphite flake spacing in the negative electrode material and the specific surface area of ​​the negative electrode material, and control the spacing within the range of 1.282-1.298nm, thereby introducing partial structural defects into the negative electrode material, allowing the negative electrode material to have a higher capacity, so that the lithium ion battery containing the negative electrode material has improved first reversible specific capacity, first cycle coulomb efficiency, rate performance, cycle performance, capacity and capacity retention rate.

[0019] (2) The method for preparing the negative electrode material provided by the present invention can reduce the lattice stress and oxygen-containing functional groups in the natural graphite in the negative electrode material through heat treatment, thereby improving the stability and capacity of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM image of the negative electrode material prepared in Example 1 of the present invention;

[0021] Figure 2 The SEM image and EDS image of the negative electrode material prepared in Example 1 of the present invention;

[0022] Figure 3 The first week charge and discharge curve of the battery assembled with Example 1 of the present invention and natural graphite bulk material at a current density of 0.1C;

[0023] Figure 4 The cycle performance diagram of the battery assembled with Example 1 of the present invention and natural graphite bulk material at a current density of 10C;

[0024] Figure 5 XRD diagram of the negative electrode material and natural graphite prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0026] A first aspect of the present invention provides a negative electrode material for a lithium ion battery, wherein the negative electrode material comprises natural graphite and aluminum chloride between natural graphite sheets;

[0027] Wherein, the interlamellar spacing of the negative electrode material is 1.282-1.298 nm.

[0028] In the present invention, the negative electrode material provided by the present invention includes natural graphite and aluminum chloride between natural graphite sheets, and the aluminum chloride exists in molecular form. Introducing aluminum chloride between natural graphite sheets can expand the natural graphite sheet spacing in the negative electrode material, thereby introducing partial structural defects in the negative electrode material, allowing the negative electrode material to have a higher capacity, so that the lithium ion battery containing the negative electrode material has improved first reversible specific capacity, first cycle coulomb efficiency, rate performance, cycle performance, capacity and capacity retention rate.

[0029] Furthermore, the interlamellar spacing of the negative electrode material is 1.289-1.294 nm.

[0030] In the present invention, the interlamellar spacing of the negative electrode material is measured by a German Bruker D8 Advance in-situ X-ray diffractometer.

[0031] In the present invention, preferably, the aluminum chloride is anhydrous aluminum chloride.

[0032] According to the present invention, based on the total weight of the negative electrode material, the negative electrode material comprises: 95.5-95.8wt% natural graphite and 4.2-4.5wt% aluminum chloride; preferably, the negative electrode material comprises: 95.6-95.7wt% natural graphite and 4.3-4.4wt% aluminum chloride.

[0033] In the present invention, when the weight of natural graphite and aluminum chloride meets the above range, it is beneficial for aluminum chloride to enter the graphite interlayer to form an intercalation compound, thereby expanding the interlayer spacing of natural graphite and enabling Li + It can be smoothly inserted into the natural graphite interlayer without destroying the natural graphite structure.

[0034] In the present invention, the weights of the natural graphite and aluminum chloride are measured using a METTLER TOLEDO electronic analytical balance ME204E and a Japanese JEOL IT-800 field emission scanning electron microscope.

[0035] According to the present invention, the particle size of the negative electrode material is 70-110 meshes, preferably 80-100 meshes.

[0036] In the present invention, when the particle size of the negative electrode material meets the above range, the negative electrode material can maintain a suitable specific surface area, thereby providing suitable lithium storage active sites, reducing the generation of side reactions, and improving the capacity of the negative electrode material.

[0037] According to the present invention, the specific surface area of ​​the negative electrode material is 6-8.5m 2 / g, preferably 7-8m 2 / g.

[0038] In the present invention, the specific surface area of ​​the negative electrode material is measured by an Italian Microtrac BEL BELSORP-mini II instrument.

[0039] In the present invention, when the specific surface area of ​​the negative electrode material satisfies the above range, the negative electrode material can provide suitable lithium storage active sites, reduce the generation of side reactions, and improve the capacity of the negative electrode material.

[0040] A second aspect of the present invention provides a method for preparing a negative electrode material for a lithium ion battery, wherein the preparation method comprises the following steps:

[0041] After mixing natural graphite and aluminum chloride, heat treatment is performed to obtain a negative electrode material;

[0042] Wherein, the mass ratio of the natural graphite to aluminum chloride is 1:(5-20);

[0043] The heat treatment conditions include: under protective gas, heating from room temperature to 160-200° C. at a heating rate of 3-8° C. / min for 5-20 hours.

[0044] In the present invention, when the mass ratio of the graphite to aluminum chloride satisfies the above range, it is conducive to fully forming a chlorine-containing atmosphere, reducing the difficulty of the intercalation reaction, and facilitating aluminum chloride to enter between graphite sheets to form an intercalation compound.

[0045] In the present invention, when the conditions of the heat treatment meet the above range, the lattice stress and oxygen-containing functional groups in the natural graphite in the negative electrode material can be reduced, thereby improving the stability and capacity of the negative electrode material.

[0046] According to the present invention, the mass ratio of graphite to aluminum chloride is 1:(10-15).

[0047] According to the present invention, the particle size of the natural graphite is 80-120 meshes, preferably 90-110 meshes.

[0048] In the present invention, when the particle size of the natural graphite meets the above range, it is beneficial for the graphite to fully contact with the gasified aluminum chloride, and it is convenient for the aluminum chloride to enter the graphite sheets to form intercalation compounds.

[0049] According to the present invention, the interlamellar spacing of the natural graphite is 0.335-0.342 nm, preferably 0.338-0.34 nm.

[0050] In the present invention, when the interlamellar spacing of the natural graphite satisfies the above range, the negative electrode material has excellent performance.

[0051] According to the present invention, the specific surface area of ​​the natural graphite is 5.4-5.8m 2 / g, preferably 5.5-5.7m 2 / g.

[0052] In the present invention, when the specific surface area of ​​the natural graphite meets the above range, it is beneficial for the graphite to fully contact with the gasified aluminum chloride, and it is convenient for the aluminum chloride to enter between the graphite sheets to form an intercalation compound.

[0053] In the present invention, preferably, the natural graphite is flake graphite.

[0054] According to the present invention, the heat treatment conditions also include: under protective gas, heating from room temperature to 160-200°C at a heating rate of 3-8°C / min for 5-20h. Room temperature refers to 25-35°C.

[0055] According to the present invention, the heat treatment conditions include: under protective gas, heating from room temperature to 170-190° C. at a heating rate of 4-6° C. / min for 9-16 hours.

[0056] According to the present invention, the protective gas is selected from argon and / or nitrogen.

[0057] According to the present invention, the heat treatment process also includes rinsing and drying. The rinsing conditions include: rinsing the heat-treated material alternately with hydrochloric acid, deionized water and ethanol; the concentration of the hydrochloric acid is 0.05-0.2 mol / L, and the solution after rinsing is neutral. The drying conditions include: the temperature is 60-100°C, preferably 75-85°C; the time is 6-12h, preferably 7-9h.

[0058] In the present invention, the solution after flushing is controlled to be neutral, and unreacted aluminum chloride or other impurities are removed, thereby improving the performance of the negative electrode material.

[0059] According to the present invention, the mixing conditions include: a rotation speed of 4000-6000 rpm, preferably 4500-5500 rpm; and a time of 5-10 min, preferably 7-8 min.

[0060] The third aspect of the present invention provides a negative electrode material prepared by the above preparation method.

[0061] A fourth aspect of the present invention provides a negative electrode plate for a lithium ion battery, wherein the negative electrode plate for the lithium ion battery comprises the negative electrode material described above.

[0062] According to the present invention, a method for preparing a negative electrode sheet of a lithium ion battery comprises the following steps:

[0063] The negative electrode material, conductive agent Super P and sodium polyacrylate were weighed and mixed into a slurry in a mass ratio of 8:1:1, coated on a copper foil, vacuum dried and rolled to form a negative electrode sheet for a lithium-ion battery.

[0064] A fifth aspect of the present invention provides a lithium ion battery, comprising the above-mentioned lithium ion battery negative electrode sheet.

[0065] According to the present invention, a method for preparing a lithium ion battery comprises the following steps:

[0066] The battery assembly is completed by using a lithium-ion battery negative electrode sheet including a negative electrode material, a metal lithium sheet as a positive electrode, Ceglard2500 as a diaphragm, and lb315 as an electrolyte.

[0067] The present invention will be described in detail below by way of examples. In the following examples,

[0068] The first reversible specific capacity, first week coulombic efficiency, rate performance, cycle performance and capacity tests were all measured by Wuhan Blue Electric CT3002A test system;

[0069]

[0070] The interlamellar spacing of the negative electrode material was measured by a German Bruker D8 Advance in-situ X-ray diffractometer;

[0071] The specific surface area was measured by the Italian MicrotracBEL BELSORP-mini II instrument;

[0072] The raw materials used in the examples and comparative examples are all commercially available.

[0073] Example 1

[0074] The particle size is 100 mesh, the interlamellar spacing is 0.339nm and the specific surface area is 5.6m 2 / g of natural graphite and anhydrous aluminum chloride in a mass ratio of 1:12 were mixed at a rotation speed of 5000 rpm for 7.5 min, and then heat-treated at a heating rate of 5°C / min from 30°C to 180°C for 10 h under argon protective gas, and then rinsed alternately with 0.12 mol / L hydrochloric acid, deionized water and ethanol until the pH of the solution was neutral, and then dried at 80°C for 8 h to obtain negative electrode material A1;

[0075] A1 was subjected to scanning electron microscopy, EDS analysis and XRD analysis. Figure 1 is a SEM image of the negative electrode material prepared in Example 1 of the present invention, Figure 1 It can be seen that the negative electrode material maintains the structure of natural graphite, and the stacked layer structure can be widely observed;

[0076] Figure 2 The SEM and EDS images of the negative electrode material prepared in Example 1 of the present invention are shown in FIG. Figure 2 It can be seen that Figure 2 Figure (a) is a SEM image of the negative electrode material prepared in Example 1. Figure 2 Figure (b) shows the distribution of Cl element. Figure 2 Figure (c) is the distribution diagram of Al element. It can be seen that Al element and Cl element are evenly distributed within the range of graphite layer and only exist within the range of graphite layer, indicating that aluminum chloride has successfully entered the graphite layer under the action of intercalation reaction;

[0077] Figure 5 The XRD diagram of the negative electrode material and natural graphite prepared in Example 1 of the present invention is shown in FIG. Figure 5 It can be seen that the peaks at 26.5° and 27.5° correspond to the (002) plane of graphite and the (001) plane of graphite intercalation compounds, respectively. The absence of high-order peaks of graphite intercalation compounds indicates that they have a lower ordered structure compared with natural graphite, indicating that AlCl3 undergoes intercalation reaction between graphite layers, but also retains a part of the original graphite sheet structure.

[0078] Example 2

[0079] The particle size is 110 mesh, the interlamellar spacing is 0.34nm and the specific surface area is 5.7m 2 / g of natural graphite and anhydrous aluminum chloride in a mass ratio of 1:15 were mixed at a rotation speed of 5500 rpm for 7 min, and then heat-treated under nitrogen protective gas at a heating rate of 6°C / min from 35°C to 190°C for 9 h. The mixture was alternately rinsed with 0.15 mol / L hydrochloric acid, deionized water and ethanol until the pH of the solution was neutral, and then dried at 85°C for 7 h to obtain the negative electrode material A2.

[0080] Example 3

[0081] The particle size is 90 mesh, the interlamellar spacing is 0.338nm and the specific surface area is 5.5m 2 / g of natural graphite and anhydrous aluminum chloride in a mass ratio of 1:10 were mixed at a rotation speed of 4500 rpm for 8 min, and then heat-treated under argon protective gas at a heating rate of 4°C / min from 30°C to 170°C for 16 h. The mixture was alternately rinsed with 0.09 mol / L hydrochloric acid, deionized water and ethanol until the pH of the solution was neutral, and then dried at 75°C for 9 h to obtain the negative electrode material A3.

[0082] Example 4

[0083] The particle size is 80 mesh, the interlamellar spacing is 0.335nm and the specific surface area is 5.4m 2 / g of natural graphite and anhydrous aluminum chloride in a mass ratio of 1:5 were mixed at a rotation speed of 4000 rpm for 10 min, and then heat-treated under argon protective gas at a heating rate of 3°C / min from 25°C to 160°C for 20 h. The solution was rinsed alternately with 0.05 mol / L hydrochloric acid, deionized water and ethanol until the pH of the solution was neutral, and then dried at 60°C for 12 h to obtain the negative electrode material A4.

[0084] Example 5

[0085] The negative electrode material was prepared according to the method of Example 1, except that the mass ratio of natural graphite to anhydrous aluminum chloride was 1:11, to obtain negative electrode material A5.

[0086] Example 6

[0087] The negative electrode material was prepared according to the method of Example 1, except that the interlayer spacing of natural graphite sheets was 0.3385 nm, and negative electrode material A6 was obtained.

[0088] Example 7

[0089] The negative electrode material was prepared according to the method of Example 1, except that the specific surface area of ​​natural graphite was 5.55 m 2 / g, and negative electrode material A7 was obtained.

[0090] Example 8

[0091] The negative electrode material was prepared according to the method of Example 1, except that: under argon protective gas, the temperature was raised from 30°C to 185°C at a heating rate of 5.5°C / min for 13 hours to obtain negative electrode material A8.

[0092] According to the analysis and characterization method of A1, negative electrode materials A2-A8 were analyzed and characterized. Aluminum chloride was successfully introduced between natural graphite sheets, which can expand the interlamellar spacing of natural graphite in the negative electrode material and the specific surface area of ​​the negative electrode material, thereby introducing some structural defects in the negative electrode material, allowing the negative electrode material to have a higher capacity, and making the lithium-ion battery containing the negative electrode material have excellent electrochemical performance.

[0093] Comparative Example 1

[0094] The negative electrode material was prepared according to the method of Example 1, except that the mass ratio of natural graphite to anhydrous aluminum chloride was 1:3, to obtain negative electrode material D1.

[0095] Comparative Example 2

[0096] The negative electrode material was prepared according to the method of Example 1, except that: under argon protective gas, the temperature was raised from 25° C. to 230° C. at a heating rate of 4° C. / min for 4 h to obtain negative electrode material D2.

[0097] Comparative Example 3

[0098] (1) Preparation of graphite intercalation compound: natural flake graphite with D50 = 15 μm is used as the host and metal aluminum chloride is used as the guest. The host and the guest are quickly mixed in a mass ratio of 1:2 and then transferred to a reactor. The reactor is placed in a heating furnace and heated at 400° C. for 72 h. After cooling, the graphite intercalation compound is obtained by washing and drying.

[0099] (2) Preparation of expanded graphite: Under an Ar gas protective atmosphere, the graphite intercalation compound is directly placed in a high-temperature furnace, heated to 1000°C at a heating rate of 10°C / min, and heated in the high-temperature area for 10s to obtain expanded graphite with expanded flakes;

[0100] (3) Deposition of nano-silicon: Expanded graphite as a carrier is placed in a fluidized bed reaction vessel, heated to 800° C., and chlorosilane is introduced at a flow rate of 3 L / min. The diluent gas is hydrogen at a flow rate of 10 L / min. The gas is allowed to enter the expanded graphite interlayers, and nano-silicon is prepared between the expanded graphite interlayers through a deposition reaction. The reaction time is controlled to 10 min to obtain an expanded graphite material with a high content of nano-silicon deposition;

[0101] (4) Pyrolytic carbon layer coating: The nano-silicon deposited expanded graphite material is placed in a rotary furnace, the temperature is raised to 900°C under an argon protective atmosphere, and acetylene gas is introduced at a flow rate of 3 L / min for chemical vapor deposition. The reaction lasts for 10 minutes to coat a uniform and dense pyrolytic carbon layer on the surface of the nano-silicon / graphite, thereby obtaining expanded natural graphite without aluminum chloride flakes, thereby obtaining the negative electrode material D3.

[0102] Test Example 1

[0103] The physical properties of the negative electrode materials in the above embodiments and comparative examples were tested.

[0104] The weights of natural graphite and aluminum chloride of the negative electrode materials were measured using a METTLER TOLEDO electronic analytical balance ME204E and a Japanese JEOL IT-800 field emission scanning electron microscope.

[0105] The results are shown in Table 1.

[0106] Table 1 Negative electrode material characteristic test results

[0107]

[0108] Test Example 2

[0109] The negative electrode materials (A1-A8 and D1-D3) prepared in Examples 1-8 and Comparative Examples 1-3 were subjected to electrochemical performance tests.

[0110] Assembling Li-ion Batteries:

[0111] (1) Weighing negative electrode materials (A1-A8 and D1-D3), conductive agent Super P and sodium polyacrylate in a mass ratio of 8:1:1, mixing to form a slurry, coating it on a copper foil, vacuum drying, and rolling to form a negative electrode sheet for a lithium-ion battery;

[0112] (2) A lithium-ion battery negative electrode sheet including a negative electrode material is used, a metal lithium sheet is used as a positive electrode, Ceglard 2500 is used as a separator, and an electrolyte is lb315 to complete the battery assembly (A1-A8 and D1-D3).

[0113] The constant current charge and discharge test of the battery is carried out using the LAND series battery test system. The test method is as follows:

[0114] After the battery was left to rest for 8 hours, it was charged and discharged at a rate of 0.1C-10C. The test voltage range was 0.005V-1.5V, and the 1C current density was defined as 372mA / g.

[0115] Table 2 Electrochemical performance test results

[0116]

[0117] Figure 3 The first week charge and discharge curve of the battery assembled with the natural graphite bulk material of Example 1 of the present invention at a current density of 0.1C is shown in FIG. Figure 3 It can be seen that the battery made of the negative electrode material prepared in Example 1 has an initial reversible specific capacity of 397.1 mAh / g and a first-week coulombic efficiency of 58.4%.

[0118] Figure 4 The cycle performance diagram of the battery assembled with the natural graphite bulk material and the embodiment 1 of the present invention at the current density of 10C is shown in FIG. Figure 4 It can be seen that the battery made of the negative electrode material prepared in Example 1 was cycled for 900 cycles at a current density of 10C, with a specific capacity of 277.9 mAh / g and a capacity retention rate of 98.6%.

[0119] pass Figure 1-5 It can be seen from the data in Tables 1-2 that the lithium ion battery prepared in Examples 1-8 of the present invention, by introducing aluminum chloride between natural graphite sheets, can expand the natural graphite sheet spacing in the negative electrode material and the specific surface area of ​​the negative electrode material, thereby introducing some structural defects into the negative electrode material; through heat treatment, the lattice stress and oxygen-containing functional groups in the natural graphite in the negative electrode material can be reduced, and the lithium ion battery prepared from the negative electrode material has an initial reversible specific capacity of up to 420.7 mAh / g, a first-week coulomb efficiency of 60.8%, a 10C / 0.1C capacity of 71%, and a capacity retention rate of 98.6% after 900 cycles, so that the button half-cell has both excellent electrochemical performance and stability.

[0120] Compared with Examples 1-8, in Comparative Example 1, the mass ratio of natural graphite to anhydrous aluminum chloride is 1:3, and the content of anhydrous aluminum chloride is low, which is not conducive to the formation of a chlorine-containing atmosphere, increases the difficulty of the intercalation reaction, and is not conducive to the aluminum chloride entering the graphite interlayer to form an intercalation compound (interlayer spacing is 0.425nm), so that the first reversible specific capacity of the lithium ion battery and the capacity retention rate after 900 cycles are both reduced; in Comparative Example 2, the heat treatment temperature is 230°C, which leads to an increase in the lattice stress and oxygen-containing functional groups in the natural graphite in the negative electrode material, so that the first reversible specific capacity of the lithium ion battery and the capacity retention rate after 900 cycles are both reduced; in Comparative Example 3, nano-silicon particles are also included, and anhydrous aluminum chloride is removed, resulting in a lack of support for aluminum chloride between the graphite sheets. As the number of battery cycles gradually increases, the graphite interlayer spacing will decrease, so that the first reversible specific capacity of the lithium ion battery and the capacity retention rate after 900 cycles are both reduced.

[0121] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A negative electrode material for a lithium ion battery, characterized in that: The negative electrode material includes natural graphite and aluminum chloride between natural graphite sheets; Wherein, the interlamellar spacing of the negative electrode material is 1.282-1.298 nm.

2. The negative electrode material according to claim 1, wherein Based on the total weight of the negative electrode material, the negative electrode material comprises: 95.5-95.8wt% natural graphite and 4.2-4.5wt% aluminum chloride; And / or, the particle size of the negative electrode material is 70-110 mesh; And / or, the specific surface area of ​​the negative electrode material is 6-8.5m 2 / g.

3. A method for preparing a negative electrode material for a lithium ion battery, characterized in that: The preparation method comprises the following steps: After mixing natural graphite and aluminum chloride, heat treatment is performed to obtain a negative electrode material; Wherein, the mass ratio of the natural graphite to aluminum chloride is 1:(5-20); The heat treatment conditions include: under protective gas, heating from room temperature to 160-200° C. at a heating rate of 3-8° C. / min for 5-20 hours.

4. The preparation method according to claim 3, wherein The mass ratio of the natural graphite to aluminum chloride is 1:(10-15); And / or, the particle size of the natural graphite is 80-120 mesh; And / or, the interlamellar spacing of the natural graphite is 0.335-0.342 nm.

5. The preparation method according to claim 3 or 4, wherein The specific surface area of ​​the natural graphite is 5.4-5.8m 2 / g.

6. The preparation method according to any one of claims 3 to 5, wherein: The heat treatment conditions include: heating from room temperature to 170-190°C at a heating rate of 4-6°C / min for 9-16h under protective gas; Preferably, the protective gas is selected from argon and / or nitrogen; And / or, the heat treatment process further includes rinsing and drying.

7. The preparation method according to any one of claims 3 to 6, wherein: The mixing conditions include: a rotation speed of 4000-6000 rpm and a mixing time of 5-10 min.

8. A negative electrode material obtained by the preparation method according to any one of claims 3 to 7.

9. A negative electrode plate for a lithium ion battery, characterized in that: The negative electrode plate of the lithium-ion battery comprises the negative electrode material described in any one of claims 1-2 and 8 above.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery negative electrode sheet according to claim 9.

Citation Information

Cited By

  • Graphite negative electrode material, preparation method thereof, lithium ion battery negative electrode plate and application of lithium ion battery negative electrode plate

    CN121377006A